PERSEPSI MASYARAKAT WONOSOBO TERHADAP AKTIVITAS PT. CPI (CHEVRON PACIFIC INDONESIA) DI KELURAHAN TALANG MANDI KECAMATAN MANDAU KABUPATEN BENGKALIS - Juspriyanti Purba; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
PUBLIC PERCEPTION OF PT ACTIVITY AGAINST WONOSOBO PT. CPI (CHEVRON PACIFIC INDONESIA) IN MANDI DISTRICT OF GUTTER VILLAGE MANDAU BENGKALIS This thesis is submitted in order to qualify holds a Bachelor of Sociology. With the title "Public Perception of PT Activity Against Wonosobo. CPI (Chevron Pacific Indonesia) in Mandi District of Gutter Village Bengkalis Saber". The problem addressed in this paper is to describe the public perception of the company's activities Limassol. Production activities undertaken by the company to have an impact on the surrounding community, both positive and negative . Vice versa, views or actions of people around the company may affect the sustainability of a company's presence in a particular area. The interaction between the two is a matter that can not be avoided because they are in the same neighborhood population of this study is the entire community of Wonosobo in RW 14 with the 1120 Soul. The sample in this study as many as 5 % of the total population, the sample in this study as many respondents with a calculation that is x 1120 = 56 respondents. The sampling technique used in this study is the technique of random sampling or random sederhanan that samples taken from each unit of study is a unit elemeter of the population has an equal chance to be selected as a sample, if desired sample size is different then the size of the opportunity for selected for each elementary unit was different too. The method used is the method of Quantitative Descriptive data analysis Quantitative and Qualitative. Screening instrument data used are observation, questionnaires , and interviews. The theory used for the public perception of this issue is by Harihanto (2001 ) as cited by Pandeangan (2005 ) stated that perception is essentially the view, interpretations, judgments, expectations or aspirations of a person to an object.Results of research conducted in general the writer can say that there is a public perception of positive impact and therefore have a negative impact felt by the surrounding community. The impact of company activities such as water pollution, air pollution and soil contamination. But people are also protected because the company continues to implement its corporate social responsibility ( CSR ) to the surrounding community. Corporate social responsibility activities are largely included in the category of charity and genuine desire to engage in activities that the company actually came from the company's vision. Keywords: perception, environmental impact, CSR programs